The Effect of Various Tricoderma sp. Isolate As TRICHOCOMPOST Fertilizer In Tomato (Lycopersicum esculentum Mill) Growth And Yield - Abdul Wachid; Laili Fitrianisyah (Universitas Muhammadiyah Sidoarjo, 2021)
The main objective of this investigation was to study the effects of TRICHOCOMPOST treatments on some vegetative growth and yield characters of tomato plants. This experiment was conducted at theyard area of Wates, Kedensari Village, Tanggulangin and Agricultural Research and Experiment Center, Muhammadiyah Sidoarjo University, during Februaryto August 2018. This research used a single factor Randomized Complete Block Design (RCBD) with compost fertilizer without Trichoderma sp. as control, Trichoderma sp. Claket isolate, Trichoderma sp. Jatijejer Isolate, dan Trichoderma sp. Jatirejo isolate as the main factor, 8 treatment levels and repeated 4 times. Then differences in the average value proceed used Honestly Significant Difference (HSD) at 5% level. The obtained results indicated generally that the effects of Trichocompost with Jatirejo isolate (P3) treatments reflected significant differences among the mean values of number of leaves plantand number of branch plant characters. Trichocompost with Jatijejer isolate (P2) reflected significant differences amongroot wet weight, Trichocompost with Jatirejo isolate (P3) reflected insignificant difference on plant characters than P0 treatment, however the treatment has the highhest mean value among the number of flower, the sum of fruit, and plant dry weight.